A hybrid muon detector design with RPC and plastic scintillator for the experiment at the Super Tau-Charm Facility. (20th September 2021) - Fang, Z.; Liu, Y.; Shi, H.; Liu, J.; Shao, M.
Abstract: The Super Tau-Charm Facility (STCF) is a high-luminosity electron-positron collider project proposed in China. STCF acts as a natural extension of the BEPCII collider. The peak luminosity of STCF is over 50 times higher than that of the BEPCII, greatly benefitting tau-charm physics research. However, it demands a high-performance detector system. To obtain an optimal balance of the μ ± identification efficiency and the rejection of charged hadron background, while maintaining a reasonable overall cost, a hybrid muon detector design consisting of three layers of bakelite-RPCs and seven layers of scintillator strips is proposed for the experiment at the STCF. Simulations using the Geant4 package indicate that, in the beam-induced background predicted for the STCF experiment, the identification efficiency for μ ± with momenta exceeding 0.8 GeV/c can be higher than 95%, with a 97% π ± rejection rate. The identification efficiency for neutrons that are not detected by the electromagnetic calorimeter exceeds 95% for a background rejection rate of 97%. These results demonstrate that the hybrid muon detector design can meet the demands for muon detection in the STCF experiment.